Theory Education in Canada: Foundational Thinkers and Texts in the Subfield1. Issue 1 (2nd January 2022) - Orr, Steven
Abstract: This article reports the results of an examination of 187 introductory political theory courses within political science departments across Canada from 2011 to 2016. While instructors and departments know what they are doing in their classrooms, this article provides a broad overview of the field of political philosophy in Canadian universities through an exploration of which texts and thinkers are considered essential, with a focus on the introductory courses that are often mandatory for political science degrees and provide the foundation for the broader discipline. The hope is that these results will provide a stronger foundation for ongoing debates about the status and merits of contemporary political theory training as can be seen in relation to Black Lives Matter, Rhodes Must Fall, and, in Canada, reconciliation efforts between Indigenous and Settler populations. Further, this article suggests that there is little emphasis on uniquely Canadian expressions of political theory at this level—and this likely has implications for the shape of the subfield in the Canadian context.